Kulturen i en mannsdominert operativ avdeling - Jon, Nina (Nordisk Tidsskrift for Kriminalvidenskab, 2025)
Abstract A new specialised unit, “Echo”, established within the Oslo Police District (OPD), is staffed by specially trained, predominantly male operational officers. Based on 213 hours of observation and 26 semi-structured qualitative interviews, this article explores the significance of Echo’s establishment and the culture that characterises the unit. During its creation, there were clear concerns within the OPD leadership that a negative culture might develop within Echo. One concern was that this predominantly male unit would foster a culture of masculinity that excluded women. Another was that a division might emerge between specialised and non-specialised officers resulting in an “A and B police force”, while a further concern was that Echo might become a “mini-SWAT” team focusing on training for rare but serious events such as terrorism and organised crime instead of patrolling and serving the city’s day-to-day needs. At a time when gender equality in Norway has improved and the roles of both women and men have changed considerably, policing culture has also undergone a transformation. Together with Echo’s leadership, characterised by a strong commitment to humility, inclusiveness and psychological safety, the unit has avoided the pitfalls of a harmful culture that the Oslo Police District’s executive leadership feared when the unit was first established.